Fifty Years of Work without Wages : Laborare est orare - Rowley, Charles (Place of publication not identified : publisher not identified, 1912)
Born in Ancoats, a deprived industrial area of Manchester, Charles Rowley (1839-1933) witnessed what he saw as the degeneration of inner-city life in the second half of the nineteenth century. His family's picture-framing business, combined with his love of culture, brought him into contact with the ideas and personalities associated with the Pre-Raphaelite Brotherhood, notably William Morris. As a social reformer, Rowley was suspicious of organised charity and its tendency to patronise those it tried to support. Through a number of progressive initiatives, he laboured to bring art and culture to working people: the Ancoats Brotherhood, which organised lectures and reading groups, was among the many projects he fostered. First published in 1911, these well-illustrated memoirs present a thoughtful portrait of Rowley's experiences and enthusiasms, touching upon his interactions with such artists as Ford Madox Brown, Dante Gabriel Rossetti and William Holman Hunt.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).